2016
DOI: 10.1177/0333102416673206
|View full text |Cite
|
Sign up to set email alerts
|

Occipital nerve stimulation improves the quality of life in medically-intractable chronic cluster headache: Results of an observational prospective study

Abstract: Background Occipital nerve stimulation (ONS) has been proposed to treat chronic medically-intractable cluster headache (iCCH) in small series of cases without evaluation of its functional and emotional impacts. Methods We report the multidimensional outcome of a large observational study of iCCH patients, treated by ONS within a nationwide multidisciplinary network ( https://clinicaltrials.gov NCT01842763), with a one-year follow-up. Prospective evaluation was performed before surgery, then three and 12 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…Some studies have also reported a reduction in the intensity of residual headaches; figures range widely, from no reduction at all, up to a 50% improvement. In the larger series, there were reductions in attack intensity of some 25% . All the 5 patients presented here experienced a reduction of 80% or more in attack frequency, with a mean reduction of 92%.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Some studies have also reported a reduction in the intensity of residual headaches; figures range widely, from no reduction at all, up to a 50% improvement. In the larger series, there were reductions in attack intensity of some 25% . All the 5 patients presented here experienced a reduction of 80% or more in attack frequency, with a mean reduction of 92%.…”
Section: Discussionmentioning
confidence: 49%
“…In three large series of tONS for CCH, attack frequencies were reduced by 46–58% . The response in migraine is relatively modest, with a reduction of less than three headache days per month when the control response is subtracted .…”
Section: Introductionmentioning
confidence: 96%
“…32 Another retrospective study, showed after a median follow-up of 17.5 months, that out of 14 CCH, three noticed a significant improvement (90%-95%), another three a moderate improvement (40%-60%), and 4 noticed a mild improvement (20%-30%). 32 Another retrospective study, showed after a median follow-up of 17.5 months, that out of 14 CCH, three noticed a significant improvement (90%-95%), another three a moderate improvement (40%-60%), and 4 noticed a mild improvement (20%-30%).…”
Section: Cluster Patientsmentioning
confidence: 97%
“…Other modalities may potentially be reported in future randomized trials. Implanted occipital nerve stimulation has been studied for cluster headache in nonrandomized studies with the suggestion of efficacy and safety . A prospective, multicenter, randomized control trial is underway in Europe to treat cluster headache using this technology .…”
Section: Neuromodulation For Cluster Headachementioning
confidence: 99%
“…Implanted occipital nerve stimulation has been studied for cluster headache in nonrandomized studies with the suggestion of efficacy and safety. [45][46][47][48][49][50] A prospective, multicenter, randomized control trial is underway in Europe to treat cluster headache using this technology. 51,52 A small study of 7 patients with chronic cluster headache also demonstrated efficacy and safety for high cervical cord stimulation but no data from any randomized trials are available.…”
Section: Occipital and Cervical Cord Nerve Stimulation-mentioning
confidence: 99%